STEM education in the Global North and Global South: competition, conformity, and convenient collaborations - Mudaly, Ronicka; Chirikure, Tamirirofa (Frontiers in Education, 2023)
Science, technology, engineering, and mathematics (STEM) education is increasingly viewed as a vehicle for global dominance and a panacea to economic downturns, environmental challenges, and food security. However, divergences in STEM education agendas at regional and national levels imply disparities in policy formulation and implementation in the Global North and Global South. This study sought to explore what informs the drivers of STEM education in the two geo-economic blocks with a view to understanding contextual factors that inform practice. A focus on STEM education in the Global North and Global South becomes necessary, given the widespread calls for collaborative work, for example, shared interests in addressing sustainable development goals, and research on the COVID-19 pandemic. A theoretical approach, based on a review of relevant literature, was adopted. Ideology critique informed the analysis and was used to make sense of the salient themes. In the Global North, STEM education is historically driven by ambitions of political dominance, the need to curb economic slumps and address critical skills shortages, and growing desire for extra-terrestrial colonization. Within this context we argue that a neoliberal agenda drives the STEM education enterprise. In the Global South, massification with equity dominates policy formulation and implementation as countries battle to redress past colonial imbalances. The Global South countries generally sign up to regional and global STEM education agendas but financial constraints compounded by an unabated brain drain result in stagnation at policy adoption at vocational level. Convenient partnerships are increasingly fashionable as countries in the Global North seek to exploit the geographical advantage of those in the Global South in order to fully utilise the extra-terrestrial space, resources for biomedical science and indigenous natural resources, among others. Collaboration endeavors between the Global North and Global South need to be mutually beneficial. The Global North needs to redistribute the aspects of power it holds in relation to STEM to move towards more equitable policies and practices across these geopolitical realms. We recommend greater vocationalisation of STEM education hinged on STEM integration with the humanities in the Global South and balanced, mutually beneficial STEM collaboration endeavors with the Global North countries.